The Effect Of Padlet Application Towards Students’ Writing Skill of Recount Text At the Tenth Grade of SMAN 1 Malingping Lebak-Banten - Cici Herminawati; Riandi Riandi; Tatu Munawaroh (Journal of English Language Learning, 2022)
This research paper aims to know whether there is a significant effect of Padlet application towards students’ writing skill of Recount text at the Tenth Grade of SMAN 1 Malingping Lebak-Banten in Academic Year 2021/2022. The research paper used the quantitative approach and quasi-experimental design. The technique in choosing the sample is cluster random sampling; the researcher used 10 IPA 4 (32 students) as class control and 10 IPA 2 (32 students) as class experimental. In the Collecting data technique, the researcher gives pre-test and post-test. In analyzing the data, the researcher used SPSS 22 statistical computation and used the result of the post-test both class control and experimental to analyze the hypotheses test. The researcher has found the result t count (-3.295) and Significant two-tailed = 0.002 < α 0.05. Therefore, the researcher concluded that the Padlet application has a good effect on Students' Writing Skills